Rural population change in China: Spatial differences, driving forces and policy implications. (April 2017) - Liu, Zhen; Liu, Shenghe; Jin, Haoran; Qi, Wei
Abstract: With the fast process of urbanization, the size of the rural population in China has changed greatly in the past few decades. This paper analyzes the trend and spatial differences of rural population change and the driving forces of this process. The main findings are summarized as follows. First, the total rural population decreased after 1995, and the size and rate of decrease follow an accelerating trend. Second, the rural population change has obvious spatial differences: some regions experience dramatic rural population decline, while others experience growth. Third, the spatial difference of rural population change is closely related to economic factors, including the per capita GDP, urbanization level, and noneconomic factors, including the rural population size and fertility level. According to our findings, we suggest that the government pay more attention to rural population change and its impacts and that narrowing the regional development gap may be the most effective way to promote sustainable development of rural areas in less developed regions. Highlights: The total of rural population turns to decrease after 1995. The changes of rural population have obvious spatial differences. The spatial differences of rural population change are closely related to economic factors. Rural population decline deserves more attention by government and scholars.